Contribution of the Teaching Staff of the College of Education at Imam Muhammad Bin Saud Islamic University in the Educational Decision Making and its Association with the Organizational Affiliation from their Viewpoint - Al-Ghamdi, Ali Marzouq (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the reality of participation of the teaching staff of the College of Education at Imam Muhammad Bin Saud Islamic University in the educational decision making from their viewpoint and its association with the organizational affiliation among them. For fulfilling the study objectives, the research used the descriptive survey method, and the study tool was by applying questionnaires for 157 participants members from the teaching staff of the College of Education at Imam Muhammad Bin Saud Islamic University in Riyadh.Main findings: overall tool of degree of contribution in decision making and its association with organizational affiliation according to responses of the teaching staff of the College of Education at Imam Muhammad Bin Saud Islamic University gained total average of (3.95/5) and at the both fields level. Also, the field of contribution of teaching staff member in decision making gained an average of (4.02/5), while the field of organizational affiliation gained an average of (3.88) and both gained a nearly high level.There’s a statistically significant correlation found between degree of contribution of the teaching staff of the College of Education at Imam Muhammad Bin Saud Islamic University in decision making and organization affiliation (P value= 0.39) which is a moderate positive correlation, in which whenever the contribution in decision making increases, the organizational affiliation increases.According to these results, a set of recommendations and suggestions are given for increasing the level of contribution and improving the organizational affiliation at Imam Muhammad Bin Saud Islamic University particularly and the Saudi Arabian and Arabic Universities generally.
Keywords: Association; Decision Making; Organization Affiliation; Imam Muhammad Bin Saud Islamic University